Matrix-assisted laser desorption/ionization analysis of lipids and high molecular weight hydrocarbons with lithium 2,5-dihydroxybenzoate matrix - Cvacka, Josef; Svatos, Ales (Rapid communications in mass spectrometry, 2003)
Lithium 2,5-dihydroxybenzoate (LiDHB) is shown to be a very effective matrix for matrix-assisted laser desorption/ionization (MALDI) analysis of nonpolar long-chain lipids, hydrocarbons and polymers. Under standard desorption and ionization conditions using a conventional nitrogen UV laser (337 nm), hydrocarbons (C(24)-C(40)), diverse lipids (triglycerides, diglycerides, wax esters from leaves) and saturated polymers are effectively lithiated providing [M+Li](+) ions. The formation of lithiated hydrocarbons is not accompanied by an elimination of hydrogen or other fragmentation reactions and, due to the relatively simple isotopic distribution of lithium, seems to be more useable for analysis of hydrocarbon mixtures than the previously used silver cationization agents. The mass calibration can be conveniently performed either externally or internally using poly(ethylene glycol) commercial standards.
Keywords: Glycerides; molekulová hmotnost; listy rostlin; Gentisates; spektrometrie hmotnostní - ionizace laserem za účasti matrice; gentisáty; Lipids; lipidy; lithium; Hydrocarbons; vosky; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; Waxes; Lithium; uhlovodíky; Molecular Weight; glyceridy; Plant Leaves